New verification possibilities for ovarian malignancies - A. E. Protasova; R. V. Orlova; G. A. Raskin (Опухоли женской репродуктивной системы, 2014)
The fact that the diagnosis can be significantly verified using the liquid-based cytology technique and immunocytochemical assain analyzed 72 cases with the ascites forms of ovarian cancer. The effective panel to diagnose ovarian adenocarcinomas with ascites may be considered as follows: Ber-EP4, calretinin for the differential diagnosis of the tumor with reactive changes, as well as estrog en receptors, WT-1, CK7 for the clarification of the type of adenocarcinoma (in case of a positive reaction to Ber-EP4). Verification of the mucinous form of adenocarcinoma is now made difficult by a negative reaction to organ-specific markers.